2001
DOI: 10.1097/00005537-200110000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Aminoglycoside Ototoxicity: A Human Temporal Bone Study

Abstract: The study suggests that aminoglycoside antibiotics can injure spiral ganglion cells directly, as well as hair cells. Thus, the characteristic hearing loss of ototoxicity can result from degeneration of either cochlear element.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…A few human temporal bone studies have described segmental degeneration and/or atrophy of the stria vascularis in deceased donors who were exposed to gentamicin, tobramycin, neomycin, or kanamycin [22, 26, 27]. Similarly, in our study, we found a smaller stria vascularis, mainly at the apical turn, in our CF group .…”
Section: Discussionsupporting
confidence: 85%
“…A few human temporal bone studies have described segmental degeneration and/or atrophy of the stria vascularis in deceased donors who were exposed to gentamicin, tobramycin, neomycin, or kanamycin [22, 26, 27]. Similarly, in our study, we found a smaller stria vascularis, mainly at the apical turn, in our CF group .…”
Section: Discussionsupporting
confidence: 85%
“…It is interesting to note that the pathology and neural degeneration seen in these cat cochleae after several years of deafness appears to be considerably more severe than the alterations one would expect in the human cochlea after equivalent periods of profound deafness even after congenital deafness (e.g., Linthicum and Anderson 1991;Nadol et al 2001). The extent and progression of hair cell loss and SGC degeneration are likely dependent on the extent and rapidity of onset of aminoglycoside-induced damage to the cochlea and possibly also on species-specific differences in neuronal survival patterns (Forge and Schacht 2000;Hinojosa et al 2001;Johnsson et al 1981;McFadden et al 2004;Sone et al 1998). The dosage of aminoglycosides in our experimental design was intentionally higher than would be used clinically to reduce the variability of the results and to provide a reliable model for profound neonatal hearing loss.…”
Section: Cochlear Pathologymentioning
confidence: 97%
“…The authors reasoned that spiral ganglion degeneration may occur, independent of hair cell damage. Hinojosa et al (2001) reported temporal bone histopathologic findings from two patients treated with gentamicin and tobramycin. Postmortem analysis revealed loss of spiral ganglion neurons and hair cells.…”
Section: Human Temporal Bone Histopathologymentioning
confidence: 99%